2018
DOI: 10.1002/slct.201801234
|View full text |Cite
|
Sign up to set email alerts
|

One‐Pot Synthesis of Au Embedded ZnO Nanorods Composite Heterostructures with Excellent Photocatalytic Properties

Abstract: Here, we have designed a noble composite nanostructure by embedding gold (Au) nanoparticles into zinc oxide (ZnO) nanorods surface in one pot synthesis as a photocatalyst. The formation the composite nanostructure was confirmed by X-ray diffraction, X-ray photoelectron spectroscopy (XPS), field emission scanning electron microscopy and transmission electron microscopy investigations. Microscopic studies suggest that spherical Au nanoparticles are nucleated on the ZnO nanorods surface. XPS shows shifting of pea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…The blue shift of the excitonic band (ZnO) in nanoflowers compared to pure ZnO (367 nm) is because of the interaction of ZnO on the Au surface. 27,28,33,71 As demonstrated earlier, the high dielectric constant of the ZnO, TiO 2 , SnO 2 , and CdSe or CdTe shell causes a red shift in the plasmonic peak of Au. 27,28,72−82 3.2.…”
Section: Resultsmentioning
confidence: 59%
See 2 more Smart Citations
“…The blue shift of the excitonic band (ZnO) in nanoflowers compared to pure ZnO (367 nm) is because of the interaction of ZnO on the Au surface. 27,28,33,71 As demonstrated earlier, the high dielectric constant of the ZnO, TiO 2 , SnO 2 , and CdSe or CdTe shell causes a red shift in the plasmonic peak of Au. 27,28,72−82 3.2.…”
Section: Resultsmentioning
confidence: 59%
“…However, the absorption peaks at 377 and 343 nm are attributed to excitonic bands for ZnO and Au/ZnO nanoflowers, respectively. The blue shift of the excitonic band (ZnO) in nanoflowers compared to pure ZnO (367 nm) is because of the interaction of ZnO on the Au surface. ,,, As demonstrated earlier, the high dielectric constant of the ZnO, TiO 2 , SnO 2 , and CdSe or CdTe shell causes a red shift in the plasmonic peak of Au. ,, …”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…[19][20][21] Studies have shown that the structure and morphology of ZnO, as a key factor, can significantly influence photocatalysis activities. [22][23][24] Recently, enormous efforts have been devoted to designing ZnO with various particles sizes and morphologies suitable for photocatalysis, including nanorods, [25] nanowires, [26] nanoribbons, [27] nanotubes [28] and three-dimensional (3D) ZnO micro/ nanostructures. [29] Especially, hierarchical 3D ZnO nanostructures are of significant interest since their novel architectural structures provide large surface area, [30] good permeability and high interfacial charge-transfer efficiency, [31,32] leading to the enhanced photocatalysis performance.…”
Section: Introductionmentioning
confidence: 99%
“…Various approaches have been utilized for the impregnation of noble metal nanoparticles in semiconductor nanostructures for visible light-driven photocatalysis, especially gold nanoparticles because of its chemical stability, intrinsic photostability during the catalytic process, and size- and shape-dependent optical sensitivity. , Several synthetic procedures, for example, hydrothermal, seed-mediated growth process, glancing-angle deposition, thermal decomposition, and sol–gel process, have been incorporated to fabricate the noble metals decorated heterostructured nanocrystals. Until now, many research groups have reported metal-decorated systems such as Pd-decorated m-BiVO 4 /BiOBr, Au-decorated V 2 O 5 @ZnO, Pd-decorated ZnO-expanded graphite, Pt-decorated PdCo@Pd/C core–shell nanoparticles, and so forth.…”
Section: Introductionmentioning
confidence: 99%